Listening and Note Taking Skills: Challenges faced by University Students in EFL Environment - Rafika Nurhidayah; Lini Fitri (LPPM STBA Pontianak, 2026)
This research paper examines the challenges faced by university students in listening and note-taking skills in an English as a Foreign Language (EFL) context. As essential components of academic success, these skills are often hindered by various linguistic and cognitive factors unique to EFL learners. The study examines difficulties such as limited vocabulary, unfamiliar accents, fast-paced lectures, and inadequate note-taking strategies. Data were collected through semi-structured interviews with EFL university students, revealing a lack of training, low confidence, and difficulties in processing spoken information while simultaneously writing notes. The findings underscore the need for pedagogical interventions that combine listening practice with explicit instruction in note-taking techniques. This study contributes to a deeper understanding of the academic support required to improve listening comprehension and note-taking efficiency among EFL students in higher education.